Les Processus Cognitifs en Counseling: Piste de Rapprochement entre Practiciens et Chercheurs - Alain, Michelle; Lecomte, Conrad (Canadian Journal of Counselling and Psychotherapy, 2011)
A study of counsellor's intentions is presented as a promising example to close the gap between research and practice in counselling. The dichotomy process/results is viewed as one factor responsible for the gap between researchers and counsellors. In this context, the study of intentions may be considered as a type of research more representative in describing and understanding counsellor's experience. A conceptual frame is presented and research implications are discussed. Finally, implications from the study of intentions are discussed, and research avenues are proposed.